Youngster’s Individual Psychological Pre¬dictors of Interpersonals Competition - Pashko, Tetyana; Anpilova, Darya (Psychological Prospects Journal, 2016)
The article presents a theoretical analysis of the psychological characteristics of the competition as a form of interpersonal interaction of subjects. The underlying determinants of the formation of the individual competition were considered: experience of sibling competition for maternal attention, tendency to certain patterns of behavior in relationships (psychological games), neurotic pride. The basic characteristics of the competition were distinguished: activating potential, a strong emotional charge, personal involvement, impaired perception opponent, etc. The individual psychological characteristics, the presence and severity of which allow to predict the likelihood of interpersonal competition and the possibility of pursuing it were analyzed: level of anxiety, self-efficacy, risk tolerance and type of achievement motivation. The results of empirical research of the competition level among modern young men and women according to the authors developed “Questionnaire self-expression of traits competitive behavior” are reported and psychodiagnostic potential is described. There we have established the fact that majority of students are peculiar: the average level of competitiveness, a high level of anxiety, a tendency hope of success in the activities, moderate risk-taking behavior, the average self-efficacy. The data obtained by correlation and factor analysis techniques for the study of individual psychological predictors of competition in adolescence are outlined. It was proved that modern students of adolescence mostly have low and medium level of competition that sets them apart from their peers-western students; competition as a phenomenon that occurs in the interaction, is negative and fraught with struggle, domination, anxiety, risk, loss of stability in the presentation of Ukrainian young people, while cooperation, its antagonist, is more associated with success, self-esteem, achievement.Keywords: competition, achievement motivation, self-efficacy, risk, guilt, shame, anxiety, juvenility, predictors.